Modeling the growth of LT and TL-oriented fatigue cracks in longitudinally and transversely pre-strained Al 2524-T3 alloy - Maduro, L. P.; Baptista, C. A R P; Torres, M. A S [UNESP]; Souza, R. C. (Elsevier, 2011)
The aluminum alloy 2524 (Al-Cu-Mg) was developed during the 90s mainly to be employed in aircraft fuselage panels, replacing the standard Al 2024. In the present analysis the fatigue crack growth (FCG) behavior of 2524-T3 was investigated, regarding the influence of three parameters: load ratio, pre strain and crack plane orientation of the material. The pre strain of aluminum alloys is usually performed in order to obtain a more homogeneous precipitates distribution, accompanied by an increase in the yield strength. In this work, it was evaluated the resistance of Al 2524-T3 sheet samples to the fatigue crack growth, having L-T and T-L crack orientations. FCG tests were performed under constant amplitude loading at three distinct positive load ratios. The three material conditions were tested: as received(AR), pre strained longitudinally (SL) and transversally (ST) in relation to rolling direction. In order to describe FCG behavior, two-parameter kinetic equations were compared: a Paris-type potential model and a new exponential equation introduced in a previous work conducted by our research group. It was observed that the exponential model, which takes into account the deviations from linearity presented by da/dN versus AK data, describes more adequately the FCG behavior of Al 224-T3 in relation to load ratio, pre strain effects and crack plane orientation. © 2011 Published by Elsevier Ltd.
Keywords: Aluminum alloys; Fatigue crack growth; Modeling; Pre strain; Aircraft fuselages; Al 2024; Al-Cu-Mg; Constant amplitude loading; Crack orientations; Crack plane; Exponential equations; Exponential models; Fatigue cracks; Kinetic equations; Load ratio; Material conditions; Potential Model; Pre-strain; Research groups; Rolling direction; Sheet samples; Three parameters; Aircraft materials; Aluminum; Cerium alloys; Cracks; Fatigue crack propagation; Fatigue of materials; Fuselages; Growth (materials); Integral equations; Mechanical engineering; Models